Inadequate humidification of respiratory gases during mechanical ventilation of the newborn. Issue 7 (July 1986) - Tarnow-Mordi, W O; Sutton, P; Wilkinson, A R
Abstract : Proximal airway humidity was measured during mechanical ventilation in 14 infants using an electronic hygrometer. Values below recommended minimum humidity of adult inspired gas were recorded on 251 of 396 occasions. Inadequate humidification, largely due to inadequate proximal airway temperature, is commoner than recognised in infants receiving mechanical ventilation.